Partição da Lipase de Geotrichum candidum em sistemas aquosos bifásicos - Junqueira, Cristina Mazzeu (2014)
The aim of this work was to study the Geotrichum candidum lipase (GcL) partition in aqueous two-phase systems (ATPSs) formed by PEG 1500, 4000 or 6000 g mol-¹ + sodium citrate + water and by triblock copolymer L35 1900 g mol-¹ + sodium citrate + water. Extracellular lipase was produced by the microorganism Geotrichum candidum NRRL Y-552 by fermentation at 30.0oC%, pH 7.0, and stirring at 250rpm. Partition studies were carried out with the surfactant from the fermented, lipase rich broth, after filtration for elimination of microorganisms. Kinetic studies and SDS-PAGE electrophoresis confirmed lipase in the fermentation stage. The influence of temperature, pH, NaCl addition, polymer molar mass, hydrophobicity of the system and compounding of the PEG and sodium citrate blend under the lipase coefficient of partition were studied. In all experiments carried out, the enzyme partitioned preferentially to the lower phase with KGcL values around 0.05-0.6. Measurements of the lipase activity in phases of ATPSs showed that there was relevant loss of the enzymatic activity during the process. Mean activity values in the upper and lower phases were of 1.5 U/ml and 5.5 U/ml, respectively, while activity in the raw broth was of 11.75 U/ml. Thermodynamic parameters of material transfer process between phases were obtained by using Van’t Hoff’s approximation in the partition studies carried out at different temperatures. The high negative value obtained for the enthalpy transfer variation point out the existence of strong interaction between the GcL and the PEG. However, the low coefficients of partition found in the ATPSs suggest that the GcL transfer process in these systems is entropically driven. The ATPSs formed by the blend PEG 1500 g mol-¹ + sodium citrate + water in pH 7.0 were optimized by the response surface methodology. The conditions that maximize the GcL partition in the lower phase were determined in extreme external conditions of PEG and sodium citrate within the concentration bands studied.